HAJI BUNKA: A CULTURAL APPROACH TO SUPPORT SOCIAL AND PHYSICAL DISTANCING POLICIES AGAINST THE COVID-19 PANDEMIC FOR STUDENTS AT THE FACULTY OF LANGUAGE AND COMMUNICATION UNIVERSITAS HARAPAN MEDAN - Mhd. Pujiono; Murniati Br. Barus; Nelvita Nelvita; Vivi Adryani Nasution; Intan Erwani (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Community service activities for students at the Faculty of Language and Communication, Universitas Harapan (FBK UNHAR) Medan to implement haji bunka towards social distancing policies amid the Covid-19 pandemic are an appropriate activity in providing an understanding of Japanese shame culture (haji bunka) for FBK UNHAR students and its implementation to prevent the spread of Covid-19. FBK UNHAR is a private higher education institution in Medan that faces challenges in implementing education on campus during the pandemic and the government's new normal performance. In this service, the team has conducted a socialization about the implementation of the haji bunka on campus, such as replacing handshakes with ojigi, wearing masks, classifying garbage, and other activities that can help prevent the spread of the coronavirus. Offline socialization activities were carried out through lecture methods and discussions with students. Following the socialization, the community service team and students agreed to incorporate the haji bunka into daily student activities on campus, as well as the protocol for implementing lectures if it is applied offline.